2000
DOI: 10.1046/j.1460-9592.2000.01661.x
|View full text |Cite
|
Sign up to set email alerts
|

High Incidence of Sudden Death with Conduction System and Myocardial Disease Due to Lamins A and C Gene Mutation

Abstract: We studied 54 living relatives from a large French kindred, among which 17 members presented with a cardiomyopathy transmitted on an autosomal dominant mode. Five of these individuals had clinical manifestations of muscle disease phenotypically consistent with Emery-Dreifuss muscular dystrophy. Genetic analysis of this kindred had demonstrated a nonsense mutation in the LMNA gene located on chromosome 1q11-q23. This gene encodes lamins A and C, proteins of the nuclear lamina located on the inner face of the nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
139
1
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(150 citation statements)
references
References 17 publications
7
139
1
3
Order By: Relevance
“…In this series of patients, who were implanted with a defibrillator in 59% of cases, male sex, non-missense mutations, and left ventricular dysfunction were associated with development of sustained ventricular tachyarrhythmias, while no relationship was found with the mode of presentation (with isolated or combination of clinical features) [24]. These findings are in line with a previous multicentre study, where a series of risk factors emerged as predictors of the occurrence of ventricular tachyarrhythmias (male gender, non- sustained ventricular tachycardia, left ventricular ejection fraction <45% and non-missense mutation), thus providing an important clinical guide for the decision to implant an ICD [53] (Table 2) [4,6,23,24,27,43,44,47,5162]…”
Section: Ventricular Tachyarrhythmias and Sudden Cardiac Deathsupporting
confidence: 78%
See 1 more Smart Citation
“…In this series of patients, who were implanted with a defibrillator in 59% of cases, male sex, non-missense mutations, and left ventricular dysfunction were associated with development of sustained ventricular tachyarrhythmias, while no relationship was found with the mode of presentation (with isolated or combination of clinical features) [24]. These findings are in line with a previous multicentre study, where a series of risk factors emerged as predictors of the occurrence of ventricular tachyarrhythmias (male gender, non- sustained ventricular tachycardia, left ventricular ejection fraction <45% and non-missense mutation), thus providing an important clinical guide for the decision to implant an ICD [53] (Table 2) [4,6,23,24,27,43,44,47,5162]…”
Section: Ventricular Tachyarrhythmias and Sudden Cardiac Deathsupporting
confidence: 78%
“…A detailed review of all the literature published on the risk of ventricular tachyarrhythmias, and on device activations in carriers of an implantable cardioverter defibrillators (ICDs) are shown in Table 2, in relationship to the series of patients with laminopathies reported in Table 1 [4,6,23,24,27,43,44,47,5162]. In the largest observational study, reported by Kumar et al [24], the cumulative occurrence of sustained ventricular tachyarrhythmias was 34% at 7 years, and among patients with no history of ventricular tachyarrhythmias the incidence was 22% during a 7-year follow-up.…”
Section: Ventricular Tachyarrhythmias and Sudden Cardiac Deathmentioning
confidence: 99%
“…Although a skeletal myopathy predominates in two of these disorders, some patients develop cardiac electrophysiologic disease, progressive left ventricular dysfunction and heart failure (11). Electrophysiologic defects usually precede DCM (12), and may be the only manifestation of cardiac involvement (13)]. Electrophysiologic abnormalities include sinus node dysfunction, progressive atrioventricular (AV) block, paroxysmal atrial fibrillation and ventricular arrhythmias [9,10,14].…”
Section: Introductionmentioning
confidence: 99%
“…Several mutations which should produce null alleles cause Emery-Dreifuss muscular dystrophy. While most missense mutations associated with these cardiac phenotypes are predicted to encode dominant negative alleles, at least one mutation [17] predicted to produce haploinsufficiency, causes familial DCM and conduction system disease [8,9,10,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…LMNA geneencoded protein products include lamin A and C, which are important components of the nucleus fiber layer and are the main cytoskeleton protein for maintaining normal nuclear membrane morphology. It has been confirmed that the first symptom of DCM induced by LMNA gene mutation is severe arrhythmia, whereas decreased heart function often appears late but progresses quickly in these patients (Bécane et al, 2000). However, in this study, most patients with IDCM were diagnosed with decreased ventricular function and heart ultrasonic LVEF was considered as an evaluation criterion.…”
Section: +mentioning
confidence: 68%